"Change Agents" on Two Wheels: Claiming Community and Contesting Spatial Inequalities through Cycling in Los Angeles. (19th August 2019) - Candipan, Jennifer
Abstract: This study uses participant observation to examine how an all‐female collective in Los Angeles uses urban cycling culture as a way to contest inequalities and advocate for social change in communities of color. Bridging the literatures on gentrification and social movements, I examine how the collective uses the bicycle as a unifying tool to draw disparate individuals together and, through the group's practices and rituals, generates a shared sense of collective identity and politicized consciousness embedded within the uneven spatial development of Los Angeles. I demonstrate how this politicized consciousness drives a collective spirit of resistance that challenges gentrification by reimagining and re‐embodying space through organized actions and everyday practices. I find that organized anti‐gentrification resistance is not merely reactionary, but rather entails pre‐figurative action and visioning for space and community. Overall, findings speak more broadly to how communities of color facing exclusion and marginalization make claims to space and community.